PENGARUH PEMBERIAN HORMON 17Î±-METILTESTOSTERON PADA PASCA PEMIJAHAN TERHADAP KEBERHASILAN MASKULINISASI IKAN GUPPY (Poecilia reticulata) - , AUFA TAQIYA, Ir. Ign. Hardaningsih, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to determine the effect of 17Î±-methyltestosterone hormone and the period after spawning of guppy parent to product maximum fry male in the process of masculinization. The research conducted in complete randomized design consisting six immersion treatments time after spawning with three replications. Immersion time of each treatment is 3, 5, 7, 9 and 11 days after the spawning period, while the control treatment was not given hormones immersion. Guppy female parent was immersed in a solution of 17Î±-methyltestosterone with 2 mg/l dose for 24 hours in accordance with the treatment after spawning period for 4 days. The results of masculinization seen after guppy fry cultured for 2 months by observing the secondary characteristics of male guppy. Data were analyzed using ANOVA and Dunnet advanced test. The results showed that giving 17Î±-methyltestosterone hormone on the period after spawning female parent guppy give effect to the success of guppies fry masculinization. Significant different results obtained in the immersion treatment 3 and 5 days after spawning compare to other treatments. The different immersion treatment time after spawning of female guppy did not affect the survival rate of fry guppies. The highest percentage of male fry obtained at the time of immersion parent guppy 3 days after spawning.